Development of an Automated Train Braking Control System Using Arduino Uno for Enhanced Community Safety - Perdinan Setia Budi (Politeknik Perkapalan Negeri Surabaya, 2023)
The contribution of the railway sector to national transportation remains relatively insignificant. The primary challenges include inadequate infrastructure and insufficient facilities. Additionally, the railway signaling network is ineffective, leading to a high rate of accidents caused by disruptions in train operations. Furthermore, the level of service provided still falls far short of public expectations. However, the rapid advancement of technology offers promising solutions. This progress is evident in various innovations, such as traffic lights, electronic devices, and the internet, which have significantly eased workloads across industries. To address these challenges, the development of an automated railway gate prototype is proposed. This system utilizes a buzzer, servo motor, LCD, LED lights, ultrasonic sensors, and Arduino UNO R3 to automatically manage the opening and closing of railway gates, enhancing operational efficiency and ensuring community safety.